Latent Classes of Principals’ Transformational Leadership and the Organizational Climate of Kindergartens - Wang, Pingping; Deng, Xinrui; Li, Xiaowei; Dong, Yuan; Jiao, Runkai (Frontiers in Psychology, 2019)
Background: Organizational climate refers to an individual's perception and experience of the climate of the work environment, and it is the most important environmental variable that affects individuals’ work performance. This study aims to classify characteristics of transformational leadership among kindergarten principals and examine their relationship to organizational climate. Methods: Convenience sampling yielded 498 kindergarten principals who completed the “Questionnaire on the Principal’s Transformational Leadership Behavior” and “Questionnaire on Organizational Climate.” Ethics approval was obtained from the Academic Ethics Committee of the College of Psychology of Northeast Normal University prior to starting the study. Results: Three latent classes were identified, including the high-level (68.8%), care-virtues (35.7%), and virtues groups (5.3%). There were significant differences in support, directive, restrictive, colleague, intimate, and disengaged behavior scores between groups. In terms of support, colleague, and intimate behavior, the high-level group had the highest scores, followed by the care-virtues group and virtues group, respectively. Regarding restrictive and disengaged behavior, the highest scores were received by the virtues group, followed by the care-virtues and high-level group, respectively. Conclusion: The study suggested that principals’ transformational leadership could be classified into three latent classes that are related to organizational climate.